Features of Professional Activity Reflection of the Olympiad "I Am a Professional" Participants - A. K. Belolutskaya; I. S. Krishtofik; V. A. Mkrtchyan (Moscow Polytechnic University, 2022)
The article presents the results of a study about the features of pre-service teachers' professional reflection. The average statistical results of the pre-service teachers who were the participants of the Olympiad "I am a professional" are considered in the context of students' professional pedagogical reflection development. The research is based on the concept of three reflection functions: research, criticism and redesign, three types of reflection: prospective, situational, retrospective, the universal competences of a teacher: cognition skills, interaction skills, self skills. The study about the features of students' professional reflection was carried out in 2021 during the period of the Olympiad "I am a professional" in the framework of three stages: planning/design, self-assessment/reflection, delayed group reflection. The sample included 261 students from universities in Moscow and other Russian regions, and 78 independent experts among acting school teachers. The methods of questioning (oral and written), content analysis, case studies, focus groups, video analysis, observation were used. As a result, the following features of students' reflection were revealed, such as: the contradictory nature of goal-setting and the determination of the necessary conditions and means when planning a lesson; the tendency to overestimate their professional strengths and not notice insufficiently formed competencies; the tendency to give exaggerated importance to the technical aspects; misunderstanding of the professional pedagogical language against the background of an intuitively adequate understanding of many pedagogical and psychological phenomena, etc. From a practical point of view, the results obtained make it possible to identify the area of professional deficiencies of pre-service teachers and set the focus for a closer examination and more thorough extensive study of evaluative, critical and other complex thinking skills, which provide a thorough professional reflection. In this regard, reflective-analytical and reflective-design work formats become significant both in the educational process and in the practical training of pre-service teachers.